Reconstruction of the depositional sedimentary environment of Oligocene deposits (Qom Formation) in the Qom Basin (northern Tethyan seaway), Iran - Safari, Amrollah; Ghanbarloo, Hossein; Mansoury, Parisa; Esfahani, Mehran Mohammadian (Geologos, 2020)
During the Rupelian–Chattian, the Qom Basin (northern seaway basin) was located between the Paratethys in the north and the southern Tethyan seaway in the south. The Oligocene deposits (Qom Formation) in the Qom Basin have been interpreted for a reconstruction of environmental conditions during deposition, as well as of the influence of local fault activities and global sea level changes expressed within the basin. We have also investigated connections between the Qom Basin and adjacent basins. Seven microfacies types have been distinguished in the former. These microfacies formed within three major depositional environments, i.e., restricted lagoon, open lagoon and open marine. Strata of the Qom Formation are suggested to have been formed in an open-shelf system. In addition, the deepening and shallowing patterns noted within the microfacies suggest the presence of three third-order sequences in the Bijegan area and two third-order depositional sequences and an incomplete depositional sequence in the Naragh area. Our analysis suggests that, during the Rupelian and Chattian stages, the depositional sequences of the Qom Basin were influenced primarily by local tectonics, while global sea level changes had a greater impact on the southern Tethyan seaway and Paratethys basins. The depositional basins of the Tethyan seaway (southern Tethyan seaway, Paratethys Basin and Qom Basin) were probably related during the Burdigalian to Langhian and early Serravallian.